The Effect of Transcranial Direct Current Stimulation and Functional Electrical Stimulation on the Lower Limb Function of Stroke Patients - Zhang, Xiao-Hua; Gu, Tao; Liu, Xuan-Wei; Han, Ping; Lv, Hui-Lan; Wang, Yu-Long; Xiao, Peng (Frontiers in Neuroscience, 2021)
Objective: This study aimed to research the effect of transcranial direct current stimulation (tDCS) and functional electrical stimulation (FES) on the lower limb function of post-convalescent stroke patients. Methods: 122 patients in the stroke recovery stage who suffered from leg dysfunction were randomly divided into two groups: a treatment group (n = 61) and a control group (n = 61). The treatment group was treated with tDCS, while the control group received FES. The lower limb Fugl-Meyer assessment (FMA), modified Barthel index (MBI), and functional ambulatory category (FAC) were used to assess the patients at three different stages: prior to treatment, four weeks after treatment, and eight weeks after treatment. Results: The assessment scores for FMA, MBI, and FAC for the lower extremities after treatment (P > 0.05) were compared with those before treatment. The FMA and MBI scores of the treatment group were significantly higher than those of the control group in all three stages (P < 0.05). The FMA, MBI, and FAC assessment scores in the treatment group were significantly higher after four weeks of treatment than before treatment, and the scores after eight weeks of treatment were significantly higher than those after four weeks after treatment (P < 0.05). The mean scores of both groups after treatment were significantly higher than those before treatment (P < 0.05). Conclusion: tDCS can significantly promote the recovery of a patient’s leg motor function in the stroke rehabilitation stage and is more effective than FES in the stroke recovery stage.